2021
DOI: 10.3390/cancers13020246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Somatic Methylation in Colonic Polyps on Risk of Developing Metachronous Advanced Colorectal Lesions

Abstract: The utility of molecular markers for predicting the risk of metachronous advanced colorectal lesions (MACLs) remains poorly investigated. We examined the relationship between somatic hypermethylation in polyps at baseline and the risk of developing MACL. This retrospective cohort study included 281 consecutive patients with colonic polyps who were enrolled between 2007 and 2009 and followed-up until 2014. MACLs were defined as adenomas of ≥10 mm, high-grade dysplasia, or with a villous component; and serrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This tight link with defective MMR system and changes in genomic methylation is often seen in LS; LS-associated adenomas and carcinomas acquire hypermethylation of select genes ( 41 ), and sometimes CIMP ( 15 , 30 ). In the sporadic setting, the presence of CIMP has been shown to associate with worse prognosis irrespective of MSI, as well as an increased risk of developing metachronous advanced colorectal lesions ( 42 , 43 ). Interestingly, Murcia et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This tight link with defective MMR system and changes in genomic methylation is often seen in LS; LS-associated adenomas and carcinomas acquire hypermethylation of select genes ( 41 ), and sometimes CIMP ( 15 , 30 ). In the sporadic setting, the presence of CIMP has been shown to associate with worse prognosis irrespective of MSI, as well as an increased risk of developing metachronous advanced colorectal lesions ( 42 , 43 ). Interestingly, Murcia et al.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Murcia et al. note that a positive CIMP status also predicted the formation of serrated polyps in unselected group of CRC patients ( 43 ). Conversely, studies of sporadic CRC cases revealed an association between frequent metastases at diagnosis and the absence of CIMP ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations